THE RELEVANCE OF REEF RESTORATION IN THE CONTINUALLY CHANGING MARINE ENVIRONMENT OF SINGAPORE - Chou, Loke Ming; Sam, Shu Qin; Toh, Tai Chong; Ng, Chin Soon Lionel (Vietnam Journal of Marine Science and Technology, 2018)
Singapore’s marine environment has changed significantly over the past five decades through coastal modification and intense human activities. More than 60% of its coral reefs have been lost to land reclamation and the remaining reefs remain exposed to increased sedimentation. Reef restoration to address habitat loss and degradation is considered viable under the changing environmental conditions based on the persisting annual coral mass spawning events, active recruitment, high species diversity and recovery from mass bleaching impacts. These ecological attributes indicate that reef ecosystem integrity is still functioning and restoration measures are relevant. An analysis of past and ongoing restoration initiatives indicates their effectiveness in improving degraded reefs as well as establishing new reef communities on modified coasts.